라식수술 후 발생한 감염성 각막염의 임상적 분석 - 김선웅; Sun Woong Kim; 변여주; Yeo Jue Byun; 김응권; Eung Kweon Kim; 김태임; Tae Im Kim (Daihan angwa haghoi jabji, 2007)
목적 : 라식 후 발생한 감염성 각막염의 임상경험을 분석하여, 종합적인 이해를 높이고자 한다. 대상과 방법 : 라식 후 각막감염증이 생긴 9명, 12안의 수술 후 발생시기, 균주, 약물치료, 수술적 치료, 최종시력을 후향적으로 조사하였다. 결과 : 세균 1안, 마이코박테리아 5안, 노카르디아 1안, 진균 1안을 확진하였으며, 균을 동정하지 못한 경우가 2명 4안이었다. 균동정에 실패한 경우를 포함하여 세균각막염은 수술 후 2일, 마이코박테리아는 평균 14.4일, 노카르디아는 4개월(수상 후 7일), 진균은 3일만에 나타났다. 세균각막염은 발현 후 즉시 진단되었고, 30일의 치료로 관해되었다. 마이코박테리아는 14일(6~55일) 후 진단되었고, 6.2개월의 치료로 관해되었으며, 5안 중 4안에서 각막편 제거를 시행하였다. 진균은 30일 후 진단되었고, 각막이식을 포함한 2.5개월의 치료 후 관해되었다. 노카르디아는 17일 후 진단되었고, 3개월 후 관해되었다. 최종시력은 세균감염의 5안중 4안, 마이코박테리아 5안 중 3안, 노카르디아 1안에서 0.5이상이었고, 진균감염 1안은 광각변별이었다. 결론 : 라식 후 발생한 세균각막염은 2일 이내에 발병하는 반면, 마이코박테리아는 14일경 발현하였다. 치료 기간은 마이코박테리아가 가장 길었으나 시력예후는 진균감염에서 가장 나빴다. <한안지 48(2):219-229, 2007> Purpose: To improve the understanding of infectous keratitis after LASIK by analyzing our clinical experiences. Methods: We retrospectively reviewed the records of 12 eyes of 9 subjects who developed infectious keratitis after LASIK, and compared them in terms of onset of symptoms, microbiologic profile, medical and surgical interventions, and final visual acuities. Results: Among them, one eye was found to have culture-proven bacterial infection, five eyes with non tuberculous mycobacterial infection, one eye with Nocardial infection, one eye with fungal keratitis and four eyes of two subjects with unisolated microorganisms. Bacterial infections included unisolated cases presenting 2 days after LASIK, mycobacteria presented at an average of 14.4 days after LASIK, Nocardia presented 4 months after LASIK (7 days after trauma), and fungus presented 3 days after LASIK. Bacterial infections were diagnosed immediately after onset of symptoms, and resolved 30 days after treatment. Mycobacterial infections were diagnosed 14 days (6-55 days) after onset and resolved after 6.2 months of treatment, which included flap amputation in 4 of 5 eyes. Fungal infections were diagnosed 30 days after onset, and resolved after 2.5 months of treatment. Norcardial infections were diagnosed 17 days after onset, and resolved after 3 months. Final visual acuities were over 0.5 in 4 of 5 cases of bacteria, in 3 of 5 cases of mycobacteria, in the 1 case of Nocardia and light perception in fungal keratitis. Conclusions: Bacterial infections tended to present within two days, whereas mycobacteria presented about 14 days after LASIK. Mycobacterial infections required the longest duration of treatment, however the visual outcome was the worst in fungal keratitis. J Korean Ophthalmol Soc 48(2):219-229, 2007